2017
DOI: 10.1242/dev.142497
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell regulation of salivary gland epithelial patterning

Abstract: Perfusion-independent regulation of epithelial pattern formation by the vasculature during organ development and regeneration is of considerable interest for application in restoring organ function. During murine submandibular salivary gland development, the vasculature co-develops with the epithelium during branching morphogenesis; however, it is not known whether the vasculature has instructive effects on the epithelium. Using pharmacological inhibitors and siRNA knockdown in embryonic organ explants, we det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 68 publications
0
49
0
5
Order By: Relevance
“…A recent report indicated the importance of endothelial factors to glandular development in mice (Kwon et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report indicated the importance of endothelial factors to glandular development in mice (Kwon et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression pattern of AQP1 seem to be important for water transport from blood vessels to SG, aiding the formation of the future salivary fluid, corroborating our results (Akamatsu et al 2003 ). In addition, recent studies on the role of vascularisation in mouse salivary glands have reported the requirement of endothelial cells for gland development by promoting expansion of specific progenitor cells during early stages (Kwon et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…These interactions are formed at the beginnings of organogenesis: the E11.5 epithelium invaginates into a condensing neural crest-derived mesenchyme containing a discontinuous CD31+ endothelial plexus and recruits SOX10+ neural precursors to form a post-ganglionic parasympathetic ganglion (Figure 2). During the next 36 h the endothelium becomes continuous and axons extend from the ganglion and travel along the developing ductal system to envelope newly forming end buds, thus forming an integrated organ system (Coughlin, 1975; Knosp et al , 2015; Knox et al , 2010; Kwon et al , 2017). As would be expected from such a heterogeneous structure, many pathways are involved in regulating epithelial branching, including those mediated by growth factors such as FGF, EGF, WNT, Hedgehog, and EDA (reviewed in Mattingly et al , 2015) and neurotransmitters acetylcholine (ACh) (Knox et al , 2010) and vasoactive intestinal protein (VIP) (Nedvetsky et al , 2014).…”
Section: Salivary Gland Developmentmentioning
confidence: 99%